MANUSIA SEBAGAI REKAN KERJA ALLAH DITINJAU DARI ENSIKLIK LABOREM EXERCENS ARTIKEL 25 - Bolilera, Fransiskus Xaverius Tola (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2019)
In everyday life humans tend to compare work with one another. One job isconsidered higher or noble compared to other jobs. Work that is cultivated byhumans every day is used as a social status. In the Encyclical LaboremExercens Article 25, it is said that all workers have the same dignity. Humandignity is obtained from God. God gives humans the dignity of work becausehumans are the image of God. As the image of God, humans are entrusted byGod to organize and maintain His creation and at the same time emulate Godwho works. In this way, God made humanity His partners in the world. AsGod's coworkers, humans must realize themselves as God's image. Thisawareness will enable humans to appreciate each other and be able to worktogether with other human beings to realize shared prosperity, so that thename of God is increasingly admired throughout the world.